Employment of phosphate solubilising bacteria on fish scales – Turning food waste into an available phosphorus source. Issue 5 (October 2019) - A. Santana, C.; Piccirillo, C.; A. Pereira, S.I.; Pullar, R.C.; Lima, S.M.; L. Castro, P.M.
Graphical abstract: Highlights: Phosphate solubilising bacteria were used on hydroxyapatite from tilapia scales. Different strains were tested, the most effective being Acidovorax oryzae . P solubilisation efficiency of almost 40% was achieved. High efficiency could be due to hydroxyapatite nanostructure (grain size 80–150 nm). This process shows potential for waste valorisation and sustainable agriculture. Abstract: The increased use of fertilisers is a well-known problem; linked to this, there is an always higher demand for phosphorus (P). Because of this, it is crucial to use P from all possible sources and, if necessary, turn it into a soluble form, available for plants/crops. In this paper we report the use of aerobic phosphate solubilising bacteria (PSB) on the scales of the tilapia ( Coptodon rendalli ) fish, a waste from the food industry; this is the first time that PSB were employed on fish scales to mediate the available P. The scales were calcined to 700 °C to obtain a nanoscale powdery material (more easily solubilised), made of hydroxyapatite, Ca10 (PO4 )6 (OH)2, a calcium phosphate with very low solubility. Seventeen different PSB strains were tested for their ability to solubilise phosphate (commercial tricalcium phosphate - TCP) and hydroxyapatite from fish scale (FSHA ). The best performing bacterial strain ( Acidovorax oryzae ZS 1–7) led to a P solubilisation more than 60 times higher than the negative control – at 325 mg/L, almost 40% of the available P was solubilised – one of the highest increased efficiencies reported for PBS. Such solubilisation was linked to a decrease of the pH to more acidic values of about 4. The strain ZS 1–7 showed higher P solubilisation efficiency with fish-derived FSHA than with commercial TCP. This approach showed a promising strategy for the valorisation of residues of the fish industry, turning them into a source of P, to be used for sustainable agriculture.